The Influence of Learning Motivation and Learning Activeness on the Mathematical Communication Ability of Grade VIII Students at MTsS Miftahussalam in the 2024–2025 Academic Year - Rahmayani Ritonga; Tanti Jumaisyaroh Siregar; Rusi Ulfa Hasanah (Journal Innovative Practices in Education (JIPE), 2026)
This study aimed to determine the description of learning motivation, learning activeness, and mathematical communication ability of Grade VIII students at MTs Miftahussalam Medan, as well as to examine the relationship among these variables. This research used a quantitative approach with a correlational method. The population of this study consisted of all Grade VIII students totaling 91 students, while the research sample consisted of 30 students who were selected using a simple random sampling technique. Data were collected using questionnaires to measure students’ learning motivation and learning activeness, and tests to measure students’ mathematical communication ability. The data obtained were analyzed using descriptive statistics and the Spearman correlation test with the assistance of the SPSS program. The results of the study showed that students’ learning motivation, learning activeness, and mathematical communication ability were in the moderate category. In addition, the results of the correlation analysis indicated that there was no significant relationship between learning motivation, learning activeness, and students’ mathematical communication ability. These findings suggested that students’ mathematical communication ability was influenced by other factors beyond motivation and learning activeness.